Cover Picture: Reversible Live‐Cell Labeling with Retro‐engineered HaloTags Enables Long‐Term High‐ and Super‐Resolution Imaging (Angew. Chem. Int. Ed. 18/2023). Issue 18 (12th April 2023) - Holtmannspötter, Michael; Wienbeuker, Eike; Dellmann, Timo; Watrinet, Isabelle; Garcia‐Sáez, Ana J.; Johnsson, Kai; Kurre, Rainer; Piehler, Jacob
Abstract : Reversible posttranslational fluorescence labeling opens exciting possibilities for advanced and superresolution microscopy techniques. In their Research Article (e202219050 ) Michael Holtmannspötter, Jacob Piehler et al. have engineered HaloTag variants with restored dehalogenase activity, which enzymatically exchange fluorogenic substrates at the second‐to‐minutes time scale. Thus, long‐term time‐lapse imaging with utmost spatial and temporal resolution is achieved with particularly striking performance in single molecule tracking and localization microscopy.